Interaction and tolerance to Alternaria brassicae in Indian mustard (Brassica juncea) genotypes: INTERACTION AND TOLERANCE TO ALTERNARIA BRASSICAE IN INDIAN MUSTARD GENOTYPES - P D MEENA,; MANJU BALA,; PANKAJ SHARMA,; DHIRAJ SINGH, (Journal of Oilseeds Research, 2014)
The biochemical changes were observed in leaves of Indian mustard tolerant (EC-399301, EC-399296, EC-399299, PHR-2) and susceptible (Varuna) genotypes infected with Alternaria blight (AB) caused by Alternaria brassicae at critical stage (75 days after sowing) of disease development. The presence of metabolites in infected B. juncea leaves such as glucosinolate (µ moles), phenol (mg/g), sugar (mg/g), protein (mg/g), carotenoids (µg/g) and chlorophyll (mg/g) were highly associated with the fungal infection. As compared to the susceptible check Varuna, level of glucosinolate, sugar, carotenoids and chlorophyll were decreased in tolerant hosts' leaves after pathogen infection. Although, the phenol and protein content in tolerant and susceptible genotypes were increased in AB infected leaves than healthy leaves. Our findings are discussed within the context of A. brassicae-B. juncea interaction and tolerance to this pathogen. The results indicated that factors conditioning the host response to A. brassicae might be the outcome of complex biochemical changes operated in host genotypes.